2023
DOI: 10.1186/s12916-022-02705-6
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged anesthesia induces neuroinflammation and complement-mediated microglial synaptic elimination involved in neurocognitive dysfunction and anxiety-like behaviors

Abstract: Background Perioperative neurocognitive disorders (PND) with a high incidence frequently occur in elderly surgical patients closely associated with prolonged anesthesia-induced neurotoxicity. The neuromorphopathological underpinnings of anesthesia-induced neurotoxicity have remained elusive. Methods Prolonged anesthesia with sevoflurane was used to establish the sevoflurane-induced neurotoxicity (SIN) animal model. Morris water maze, elevated plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…Second, the electrophysiology of synapses such as long-term potentiation/depression, EEG changes, or burst suppression was not measured. Previous studies have demonstrated that sevoflurane impaired synapse development and electrophysiological activity [ 23 , 61 64 ]. Last, we used intraperitoneal injection of ANX005 and NADNA to inhibit the expression of C1q and sialidase respectively, and we did not perform interventions at the gene and transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the electrophysiology of synapses such as long-term potentiation/depression, EEG changes, or burst suppression was not measured. Previous studies have demonstrated that sevoflurane impaired synapse development and electrophysiological activity [ 23 , 61 64 ]. Last, we used intraperitoneal injection of ANX005 and NADNA to inhibit the expression of C1q and sialidase respectively, and we did not perform interventions at the gene and transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%
“…C1q is the initiating protein in the complement cascade. A recent study showed that prolonged sevoflurane exposure increased C1q expression in the rat hippocampus, and deletion of C1q prevented microglial synaptic engulfment to alleviate cognitive dysfunction [ 23 ]. Several factors affect the binding of C1q to synapses, such as CD47, neuronal pentraxins, and sialic acids [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs used for induction of general anesthesia, such as isoflurane, suppress LPS-induced expression of microglial pro-inflammatory cytokine IL-1β in mouse brains ( Tanaka et al, 2013 ). On the other hand, prolonged anesthesia using sevoflurane induces neuroinflammation by triggering the NF-κB pathway, activates microglia, and alters their morphology in the hippocampus of aged rats ( Xu et al, 2023 ). According to Brambrink et al (2012) , exposure to isoflurane for 5 h causes apoptosis of oligodendrocytes (estimated at 6.3% of the total oligodendrocyte population) in neonatal primate brains ( Brambrink et al, 2012 ).…”
Section: Factors Affecting Traumatic Brain Injury Outcome In Experimentsmentioning
confidence: 99%
“…Under physiological conditions, microglia play a crucial role in the process of synaptic pruning, which maintains the integrity of neural circuits. However, under pathological conditions, activated microglia can lead to excessive synaptic phagocytosis, resulting in the loss of synapses and consequent cognitive impairment [135] , [136] , [137] . In mice with chronic social defeat stress-induced depression, there is evidence of excessive synaptic pruning, which is attributed to microglia-dependent synaptic phagocytosis [138] .…”
Section: Immune Dysfunction In Depressive Disordermentioning
confidence: 99%